How Effective Leadership Mediates the Influence of Organizational Culture, Governance, and Integrity on Employee Performance - M. M, Kusnadi; Hidayah, Isti; Pramono, Suwito Eko; Sutopo, Yeri (Journal of Ecohumanism, 2024)
This research analyzes the mediating role of leadership in connecting organizational culture, governance, integrity, and public servant effectiveness. By using a stratified proportional random sampling technique, data was collected from 181 employees at KSOP offices and examined using SmartPLS 4.0 for Structural Equation Modeling (SEM-PLS). The results uncovered that while organizational culture and governance independently exhibited restricted immediate influence on staff performance, integrity and leadership demonstrated noteworthy impacts. Leadership was found to facilitate the relationship between integrity and performance, emphasizing the significance of ethical and transparent practices. This study offers theoretical and practical understandings, accentuating leadership as a pivotal lever for enhancing organizational principles, governance frameworks, and integrity, thereby bettering general worker performance. These conclusions add to developing incorporated models that synchronize leadership strategies with organizational goals to cultivate sustainable public sector performance.